(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Introduction. Patients with refractory glaucoma complicated by bullous keratopathy often suffer from insupportable pain and uncomfortable sensations in the eye, and visual acuity loss, which worsens the patients’ quality of life. Purpose. To study the efficacy of a complex treatment of patients with refractory glaucoma complicated by bullous keratopathy through transscleral cyclophotocoagulation (TS CPC ) (λ=1.06 µm) followed by laser stimulation for corneal regeneration (λ=0.63 µm) and in combination with a preservative-free tear substitute bio-protector, containing 3% trehalose and 0.15% sodium hyaluronate. Material and Methods. 23 patients (23 eyes) with refractory glaucoma complicated by bullous keratopathy were treated. TS CPC was performed using neodymium laser (λ=1.06 µm; 3 sessions). On completion of a TS CPC course, each patient underwent a course of helium-neon laser stimulation of the cornea (λ=0.63 µm, t=300 sec, 10 sessions) and a 3-month course of a bio-protective tear substitute, containing 3% trehalose and 0.15% sodium hyaluronate (1 drop thrice a day). Each patient underwent visual acuity assessment, IOP measurement, Ocular Surface Disease Index (OSDI) evaluation before treatment, after a course of TCCSC, and after a three-month follow-up. Results. The TS CPC course resulted in pain management in all patients. The post-treatment IOP level decreased to 26.0 mmHg, by 30%, as compared to pre-treatment IOP level and remained stable at 3 months. Visual acuity improved in 10 of 23 patients (43%). Dry eye severity decreased by 34% (OSDI=59.4 scores). Conclusions. The patients with refractory glaucoma complicated by bullous keratopathy had a significantly decreased IOP level (by 30% in 65% of the patients) after a TS CPC course. The following laser stimulation of the cornea in combination with a course of preservative-free tear substitute, containing 3% trehalose and 0.15% sodium hyaluronate, decreased the severity of dry eye disease and corneal syndrome by 34% and significantly improved the patients’ quality of life.